Social Capital, Institutional Change, and Rural Development in Transmigration Area, West Muna Regency, Indonesia - Rozuli, Ahmad Imron; Afala, La Ode Machdani; Haboddin, Muhtar; Chawa, Anif Fatma (Masyarakat: Jurnal Sosiologi, 2024)
This study examines the development process in transmigration areas, utilizing the social capital concept in the study of three transmigration villages: Mekar Jaya, Wapae, and Suka Damai. We interviewed stakeholders, made observations, and analysed documents to collect data. Our findings highlight the important role of social capital and institutional change in supporting village development. Three critical factors emerged: First, village development involves the transfer of skills from the area of origin to the area of migration endowed with strong work ethics (etos kerja), particularly in agricultural and business sectors. Second, strong networks formed through ethnic and religious ties facilitate information sharing and cooperation, aligning the interests of the community and the village govenrment. Third, institutional changes in village autonomy and regional expansion significantly influence the village development process, strengthening communities’ social capital while reshaping the state-society relationship to become more democratic. Despite some progress, the village transformation, however, has yet to have a significant impact on improving the community’s prosperity.